2019
DOI: 10.3390/coatings9080464
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of YSZ Coatings Deposited by Plasma Spray–Physical Vapor Deposition

Abstract: The plasma spray-physical vapor deposition (PS-PVD) process has received considerable attention due to its non-line of sight deposition ability, high deposition rates, and cost efficiency. Compared with electron beam-physical vapor deposition (EB-PVD), PS-PVD can also prepare thermal barrier coatings (TBCs) with columnar microstructures. In this paper, yttria-stabilized zirconia (YSZ) coatings were fabricated by PS-PVD. Results showed that the as-deposited coating presented a typical columnar structure and was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…By comparison, the YSZ structure near the cooler grip end (Figure 7B) showed that most porosity was highly aligned along the initial column boundaries. In general, these morphologies mirror those described in a recent study of PS‐PVD YSZ coatings 36 …”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…By comparison, the YSZ structure near the cooler grip end (Figure 7B) showed that most porosity was highly aligned along the initial column boundaries. In general, these morphologies mirror those described in a recent study of PS‐PVD YSZ coatings 36 …”
Section: Resultssupporting
confidence: 86%
“…Furthermore the 1300°C/500 hours burner sample became primarily cubic with neither tetragonal phase and little monoclinic. Further comparisons are available in the recent PS‐PVD phase stability study that did show transformation to monoclinic 36 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The TGO layer acts as a protective layer to retard the thermal and oxidation diffusion. However, the TGO layer may increase the internal stress in TBC systems, which causes potential cracking at the interface between the bond and top coats, eventually leading to spallation or delamination of the top coat [7][8][9][10]. The bond coat in a TBC system is to ensure the 2 of 15 structural integrity and to protect the superalloy substrate from oxidation.…”
Section: Introductionmentioning
confidence: 99%